Resident doctors’ perception and practice of resin-bonded bridges (2019)
Background: Resin bonded bridges (RBB) was introduced as an alternative to conventional bridges for tooth replacement under certain clinical conditions. It was designed as a temporary restoration which is reversible and the clinicians’ major concern has been its longevity. The major cause of failure was attributed to de-bonding caused by complex multi- directional inter-abutment stresses associated with the 3-unit bridge that challenges the retainer and adhesive bond. The study aimed to assess the attitude, knowledge and practice of resident doctors on the performance factors of RBB. Methods: A cross-sectional study conducted amongst residents at an update course using self –administered questionnaires. The first part of the questionnaire consisted of questions related to participants’ sociodemographics, intended area of expertise, years of experience and percentage of RBBs performed in their clinical prosthodontic / restorative practice. The second part of the questionnaire comprised closeended multiple-choice questions which were designed to extract the opinion and understanding of the respondents regarding performance factor for RBBs. The questions were related to clinical indications, prosthesis design etc Results: Eighty percent of the participants indicated that had <10% tooth replacement service was done with RBB, 44.7% of the respondents considered RBB as a provisional restoration while 28 (36.8%) regarded RBB as both provisional and permanent restoration. About 76% of the respondents believe that perforated retainers were associated with clinical success of RBBs. 70% considered anterior maxilla as the most favorable location while class 1 jaw relation was preferred by 60% of participants Conclusion: With less than 10% of teeth replacement done using RBBs, there is a need for continuing education opportunities for practicing dentists and better exposure of undergraduate and postgraduate students to clinical application of RBBs